Investigação ultraestrutural e nanomecânica de glóbulos vermelhos com alterações morfológicas precoces de portadores de anemias hemolíticas - AMORIM, Maria do Socorro do Nascimento (2021)
Several diseases characterized by alterations in the biomechanical properties of erythrocytes are observed. Hemolytic anemia is a classic example, being the most prevalent hereditary disease in the world. Sickle Cell Anemia and Thalassemia are types of hemolytic anemia caused by alterations in the structure of hemoglobin, a molecule present in erythrocytes and responsible for carrying out its primary function: the transport of oxygen. Sickle cell diseases have a patho- logical origin in the synthesis of an abnormal hemoglobin, HbS, while thalassemia results in the extinction or decrease in the synthesis of normal α and β chains, which make up hemoglobin. A more detailed study, at the subcellular level, can bring new information about the pathogenesis and evolution of these diseases. Using the potential Atomic Force Microscopy techniques to probe physical properties at the nanoscale level, in this work, we investigated the biophysical properties of erythrocytes from healthy donors compared to those from individuals with diffe- rent mutations of Sickle Cell Anemia and Thalassemia. Such samples were obtained through a partnership established with HEMOMAR. The results reveal that specific properties, such as membrane roughness and cell stiffness, undergo changes, even at an early stage of disease.The results obtained in samples of sickle cell trait (HbAS), particularly, are noteworthy, in which des- pite this type of hemoglobin is considered normal, however, significant changes in its membrane properties, such as stiffness, adhesion and roughness, bring new perspectives for understanding this mutation that may aid in elucidating, for example, rising death events associated with indi- viduals that have this hemoglobin type. This work resulted in the biomolecular description and biomechanical signatures of the Sickle Cell Anemia and Thalassemia genotypes, which, in the future, may help in determining a more accurate biophysical description and in the diagnosis and clinical prognosis of these diseases.